Electrochemical Reduction of Aldehydes and Ketones for the Synthesis of Alcohols and Diols under Ambient Conditions - Wang, Lei; Zhang, Xiao; Xia, Raymond Yang; Yang, Chao; Guo, Lin; Xia, Wujiong (Synlett, 2022)
A sustainable, practical, and direct strategy for the reduction of carbonyl compounds, including aldehydes and ketones, by an electrochemical pathway is presented, affording a variety of alcohols or diols as major products with decent yields. The reaction proceeds smoothly in the air at ambient temperatures with DABCO as the sacrificial reductant. Mechanistic studies revealed that direct electrochemical reduction followed by either protonation or radical–radical homocoupling is the main pathway.
Keywords: electrochemistry; reduction; transition-metal-free; alcohols; pinacols; carbonyl compounds